The divided family - Brunstetter, Wanda E. (Brunstetter, Wanda E. Amish millionaire, 2016)
"Meet businessman Joel Byler who has gotten himself into a financial bind and his eccentric, wealthy Amish father who is done bailing out his spoiled son. When will Joel learn he most pay for his own mistakes--and at what cost to his business, his fiancée, and his Amish siblings?"-- Provided by publisher.